Activity of Phosvitin in Hydroxyapatite Acid-Damage Immersion and Antimicrobial Assays. (26th October 2020) - Shipman, Richard D.; Doering, Sean D.; Hemsath, Jack R.; Lee, Eun Joo; Grant, Jennifer E.
Abstract : Phosvitin, the most highly phosphorylated metal-binding protein found in nature, binds more than 100 calcium ions, and has been identified as an agent that could be used to generate biomineralization scaffolds. Because of published reports describing phosvitin's affinity for calcium and potential antibiotic activity, this study was undertaken in order to evaluate phosvitin for both antibiotic activity against common microorganisms and the ability to protect hydroxyapatite surfaces from acid damage. To more clearly define its antibiotic action, the effects of phosvitin on Micrococcus luteus, P. mirabilis, B. cereus, E. coli, and S. epidermidis were evaluated. In both Kirby–Bauer tests and liquid culture growth inhibition assays, phosvitin inhibited M. luteus, a microorganism that thrives in the human mouth, but not the other bacteria tested. The MIC of phosvitin was determined to be 31.3  μ g/mL when delivered in 1 mM CaCl2 but was 0.5 mg/mL in the absence of added calcium. Expanding on the potential impacts of phosvitin on the mouth, its action was evaluated in a model of tooth decay represented by acid-damaged hydroxyapatite discs. SEM, AFM, and FAAS analyses revealed that pretreatment of discs with phosvitin modulated the damage-induced morphology and topography changes associated with acid-damaged discs.